Analysis of the Effect of Hashtag "Sharia" on Customer Satisfaction with Consumer Category of Sharia Banks and Conventional Banks as Moderating Variables - Lili Supriyadi; Deni Pandu Nugraha (Enrichment : Journal of Management, 2021)
This study aims to analyze the influence of "sharia" hashtags on customer satisfaction and the influence of the "sharia" hashtag on customer satisfaction moderated by the bank category. The research method uses a questionnaire survey and partial least square testing with bogor and south tanggerang area respondents. The results revealed that hashtag "sharia" affects customer satisfaction, other research results also revealed the category of banks can strengthen the influence of hashtag "sharia" on customer satisfaction.